Community Structure of Pomacentridae fish in Coastal Waters on Malalayang Dua Village of Manado Gulf - Valdino M E Rungkat; Jan FWS Tamanampo; Jhon L Tombokan (Sam Ratulangi University, 2013)
ABSTRACT This study was conducted to determine the species composition and commu-nity structure of Pomacentridae (relative density, diversity, dominance and even-ness of species). This research was conducted in waters of the Manado Bay, at Kelurahan Malalayang Dua shore, on August 14th, 2012. The studies was conduc-ted on 2 sites, one has 3 meters depth (01o27'40.5